Case Report: A case of spinal muscular atrophy with extensively drug-resistant Acinetobacter baumannii pneumonia treated with nebulization combined with intravenous polymyxin B: experience and a literature review - Cao, Bingqing; Cao, Ling (Frontiers in Cellular and Infection Microbiology, 2023)
Spinal muscular atrophy (SMA) is a neurodegenerative disease that results in progressive and symmetric muscle weakness and atrophy of the proximal limbs and trunk due to degeneration of spinal alpha-motor neurons. Children are classified into types 1–3, from severe to mild, according to the time of onset and motor ability. Children with type 1 are the most severe, are unable to sit independently, and experience a series of respiratory problems, such as hypoventilation, reduced cough, and sputum congestion. Respiratory failure is easily complicated by respiratory infections and is a major cause of death in children with SMA. Most type 1 children die within 2 years of age. Type 1 children with SMA usually require hospitalization for lower respiratory tract infections and invasive ventilator-assisted ventilation in severe cases. These children are frequently infected with drug-resistant bacteria due to repeated hospitalizations and require long hospital stays requiring invasive ventilation. In this paper, we report a case of nebulization combined with intravenous polymyxin B in a child with spinal muscular atrophy with extensively drug-resistant Acinetobacter baumannii pneumonia, hoping to provide a reference for the treatment of children with extensively drug-resistant Acinetobacter baumannii pneumonia.